Knowledge and attitude of schoolgirls about illegal abortions in Goma, Democratic Republic of Congo - Lussy J. Paluku; Langalibalele H. Mabuza; Patrick M.H. Maduna; John V. Ndimande (AOSIS, 2010)
Background: Adolescent sexual activity, early pregnancy, induced abortion and the increase in HIV infection have become major concerns in sub-Saharan Africa and understanding adolescent sexual behaviour remains a challenge. In the Democratic Republic of Congo (DRC), the practice of illegal abortions is prevalent among school-going adolescent girls with unplanned pregnancies. Assessing their attitude and knowledge on the subject could be a starting point from which to address the problem. Objectives: To determine the knowledge of schoolgirls in Goma, DRC about the health consequences of illegal abortions and to assess their attitude towards these abortions. Method: A descriptive cross-sectional study was conducted among a randomly selected sample of 328 high school girls aged 16 to 20 years. A pre-tested, self-administered questionnaire was used for data collection. Nine out of 55 (11 public and 44 private) secondary schools were randomly selected for inclusion in the study. The Epi-Info 2000 computer program was used for data capturing and analysis. Results: The different sources of information were the radio (66.2%, 217), friends (31.7%, 104), parents (1.5%, 5), and the church (0.5%, 2). The health consequences of illegal abortion mentioned were death, infertility, infection and bleeding. Of the participants, 9.8% (32) had committed an abortion before and 46% (151) knew where to obtain it; 76.2% (250) of participants were against illegal abortion, while 23.8% (78) supported it. Conclusion: Girls in secondary school in Goma had good knowledge of the illegal abortion practice and its consequences. A fifth of them were in support of the procedure. The DRC government may need to consider legalising abortion to secure a healthy future for affected girls.